Lightweight multifunctional stone-like paint and production process thereof
By introducing modified emulsions, red rubber emulsions, active fillers and functional monomers into imitation stone paint, the problems of insufficient weather resistance, waterproofing and thermal insulation performance of existing imitation stone paints are solved, and higher physics is achieved Performance and environmentally friendly characteristics.
Patent Information
- Application Number
- CN202411712189.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-14
AI Technical Summary
The existing imitation stone paint does not perform well in harsh environments, has insufficient weather resistance, waterproofing and thermal insulation performance, and has environmental problems and human health risks.
Develop a lightweight multifunctional imitation stone paint. By introducing modified emulsions, red rubber emulsions, active fillers, functional monomers and natural colored sand, and adopting specific production process steps to form excellent physical properties and environmentally friendly characteristics. product.
It improves the waterproofing, thermal insulation and aging resistance of imitation stone paint, extends the service life of the paint film, and enhances the environmental friendliness and safety of human health.
Smart Images

Figure BDA0005156031290000171 
Figure BDA0005156031290000181
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of building decoration, and in particular to a lightweight and multifunctional stone-like paint and a production process thereof. Background Art
[0002] Imitation stone paint, as a wall decoration material, is favored for its realistic decorative effects close to natural marble and granite and rich natural colors. It is particularly suitable for the walls of various buildings, especially exterior walls and curved structures. However, when imitation stone paint is used in scenes with harsh environments such as exterior walls, it faces challenges such as strong light, large temperature changes and poor air quality, which can easily lead to aging of the paint film and performance degradation. The imitation stone paint currently on the market performs generally in terms of physical properties. Its overall mechanical properties, weather resistance and other qualities cannot fully meet the needs, and there are also environmental issues and potential risks to human health. Therefore, it will be a significant task to innovate on the basis of existing technologies and develop an environmentally friendly, highly weather-resistant and waterproof imitation stone paint that has both excellent physical properties and is environmentally friendly. Summary of the invention
[0003] In order to solve the problems of poor weather resistance, poor heat insulation and waterproof performance of imitation stone paint, the present application provides a lightweight and multifunctional imitation stone paint and a production process thereof.
[0004] The technical solution of this application is as follows:
[0005] In the first aspect, the present application provides a lightweight multifunctional stone-like paint, comprising the following raw materials in parts by weight: 60-100 parts of modified latex, 40-60 parts of red rubber latex, 50-80 parts of active filler, 1-3 parts of hydroxyethyl cellulose, 8-15 parts of antifreeze, 4-8 parts of film-forming aid, 1-3 parts of preservative, 1-2 parts of pH regulator, 450-650 parts of natural colored sand, 1-2 parts of thickener, and 100-200 parts of deionized water.
[0006] Preferably, the modified latex is prepared by compounding modified acrylic latex and styrene in a mass ratio of 1-3:2.
[0007] Preferably, the modified acrylic emulsion is prepared by the following method:
[0008] A1. Weigh the following raw materials in parts by weight: 30-40 parts of methyl methacrylate, 15-35 parts of 2-ethylhexyl acrylate, 8-12 parts of hexafluorobutyl methacrylate, 5-10 parts of 4-allyloxy-2-hydroxybenzophenone, 1-3 parts of sodium dodecylbenzenesulfonate, 6-8 parts of functional monomers, 0.2-0.6 parts of ammonium persulfate, 0.5-1 parts of saturated sodium dihydrogen phosphate solution and 80-100 parts of deionized water;
[0009] A2. Mix sodium dodecylbenzene sulfonate, deionized water, methyl methacrylate, 2-ethylhexyl acrylate, 4-allyloxy-2-hydroxybenzophenone, hexafluorobutyl methacrylate and functional monomer in parts by weight, and stir for 10-15 minutes to obtain a mixed solution a.
[0010] A3. Heat the mixed solution a to 80-100° C. under protective gas, add ammonium persulfate and saturated sodium dihydrogen phosphate solution to the mixed solution a, stir and react for 60-90 minutes to obtain a modified acrylic emulsion.
[0011] Preferably, the functional monomer is prepared by the following method:
[0012] Step 1, 3,4-dimethoxycinnamic acid, 5-chloro-2-mercaptobenzothiazole and dimethylformamide are mixed, heated and stirred for 4-6 hours, cooled to room temperature, the solvent is removed, and anhydrous ethanol is added for recrystallization to obtain an intermediate product, wherein the mass ratio of 3,4-dimethoxycinnamic acid, 5-chloro-2-mercaptobenzothiazole and dimethylformamide is 3-5:4-7:40-60;
[0013] Step 2, mixing the intermediate product with anhydrous ethanol, stirring evenly to obtain a mixed solution 1; mixing dimethylformamide, hydroxyl-terminated methyl vinyl silicone oil and sodium hydroxide, stirring for 5-8 minutes, to obtain a mixed solution 2;
[0014] Step 3, weighing mixed solution 1 and mixed solution 2 in a mass ratio of 10:8-12, adding mixed solution 2 to mixed solution 1, stirring and reacting for 4-6 hours, then adding maleic anhydride, reacting for 25-35 minutes, cooling to obtain a mixed solution, extracting, washing, and drying to obtain a functional monomer.
[0015] Preferably, the mass ratio of the intermediate product in step 2 to anhydrous ethanol is 10-15:60-70.
[0016] Preferably, the mass ratio of dimethylformamide, hydroxyl-terminated methyl vinyl silicone oil and sodium hydroxide in step 2 is 60-70:0.5-1:0.1-0.2.
[0017] Preferably, the mass of maleic anhydride in step 3 is 2-2.5% of the mass of the mixed solution 1.
[0018] Preferably, the active filler is prepared by surface treating the filler, specifically, adding the filler into a chitosan acetic acid solution, heating and stirring for 4-6 hours, filtering and drying to obtain the active filler.
[0019] Preferably, the mass ratio of the filler to the chitosan acetic acid solution is 1-4:40-60.
[0020] Preferably, the chitosan acetic acid solution is prepared by compounding chitosan, acetic acid and deionized water in a mass ratio of 5-7:10-15:80-90.
[0021] Preferably, the filler is prepared by compounding white bleached beads and hollow microbeads in a mass ratio of 4-6:1-2.
[0022] Preferably, the natural colored sand is a compound of coarse colored sand, medium colored sand and fine colored sand in a mass ratio of 1-2:10-12:2-4, the coarse colored sand is 40-60 mesh, the medium colored sand is 80-100 mesh, and the fine colored sand is 120-140 mesh.
[0023] The present application also provides a production process of a lightweight multifunctional stone-like paint, comprising the following steps:
[0024] S1. Mix hydroxyethyl cellulose, active filler and deionized water, stir evenly, add pH regulator, and continue stirring for 15-25 minutes to obtain a mixed system;
[0025] S2. Add preservative, antifreeze agent, film-forming aid, modified emulsion and red rubber emulsion to the mixed system in sequence while stirring, and stir for 20-30 minutes to obtain a base paint;
[0026] S3. Add natural colored sand to the base paint while stirring, stir evenly, then add thickener and stir for 20-25 minutes to obtain lightweight and multifunctional imitation stone paint.
[0027] Preferably, the stirring rate in step S1 is 800-1000 rpm; the stirring rate in steps S2 and S3 is 500-600 r / min.
[0028] Preferably, the antifreeze agent is ethylene glycol; the film-forming aid is dodecyl alcohol; the preservative is methyl paraben; the pH regulator is an organic alcohol amine; and the thickener is an associative thickener.
[0029] In summary, this application has the following beneficial effects:
[0030] In the present application, 3,4-dimethoxycinnamic acid and 5-chloro-2-mercaptobenzothiazole are reacted to obtain an intermediate product, and then the intermediate product is reacted with hydroxyl-terminated methyl vinyl silicone oil and maleic anhydride to obtain a functional monomer. The functional monomer is introduced during the preparation process of the acrylic emulsion, which can improve the weather resistance, water resistance, yellowing resistance and flexibility of the acrylic emulsion. The benzene ring and methoxy structure in the functional monomer can reduce the damage of ultraviolet rays to the acrylic emulsion, and the heterocyclic structure in the structure can enhance the tolerance of the emulsion. The introduction of maleic anhydride to participate in the cross-linking reaction further improves the stability of the emulsion, is not prone to aging, and extends the service life of the emulsion; the introduction of hydroxyl-terminated methyl vinyl silicone oil can effectively adjust the flexibility of the acrylic emulsion, thereby improving the comprehensive performance of the emulsion; the functional groups such as the carboxyl group of maleic anhydride and 3,4-dimethoxycinnamic acid can react with other components in the acrylic emulsion to form a more stable chemical structure, which can improve the resistance of the emulsion to chemical substances such as acids, alkalis, and salts. The modified acrylic emulsion is prepared by mixing the modified acrylic emulsion and styrene, which further enhances the resistance of the emulsion to chemical substances. Styrene has good compatibility with the monomers in the modified acrylic emulsion. After mixing, it can improve the film-forming properties of the emulsion and enhance the adhesion of the imitation stone paint.
[0031] In the present application, white bleached beads and hollow microbeads are treated with chitosan acetic acid solution to prepare active fillers. After the active treatment, chitosan can interact with the active groups in the modified latex, thereby allowing the filler to be evenly dispersed in the imitation stone paint and reducing the occurrence of defects and cracks at the interface of the imitation stone paint. The hydrophilicity of the white bleached beads and hollow microbeads is low, thereby improving the water resistance of the imitation stone paint. The combination of the white bleached beads and hollow microbeads can further enhance the thermal insulation performance of the imitation stone paint.
[0032] The lightweight multifunctional stone-like paint prepared in the present application has excellent waterproof performance, heat insulation performance and aging resistance. The introduction of functional monomers into the modified emulsion not only enhances the waterproof performance, stability performance and aging resistance of the stone-like paint, but also can effectively prevent the agglomeration of natural colored sand and promote the dispersion of colored sand in the system. The active groups in the functional monomers can help prevent oxygen from contacting the pigments in the colored sand, thereby extending the durability of the colored sand. The modified emulsion containing the functional monomers can also fill the gaps between the colored sand particles, thereby ensuring the consistency of color. DETAILED DESCRIPTION
[0033] The present application is further described in detail below in conjunction with the examples. Unless otherwise specified, the materials, reagents, etc. used in the present application can be obtained from commercial sources.
[0034] Red rubber latex was purchased from Badfu Group Co., Ltd.; acrylic emulsion was purchased from Shanghai Baolijia New Materials Co., Ltd.; hydroxyethyl cellulose was purchased from Luzhou Northern Cellulose Co., Ltd.; ethylene glycol was purchased from Shijiazhuang Jinchuan Chemical Co., Ltd.; organic alcohol amines were purchased from Shijiazhuang Jinchuan Chemical Co., Ltd.; dodecanol esters were purchased from Dena Chemical Binhai Co., Ltd.; natural colored sand was purchased from Shaanxi Shunbo Mineral Co., Ltd.; hollow microspheres were purchased from Shanghai Xianglan Chemical Co., Ltd., true density: 0.25 g / cc, particle size: 55-105 μm; white bleached beads were purchased from Shaanxi Shunbo Mineral Co., Ltd.; associative thickeners were purchased from Guangdong Yuemei Chemical Co., Ltd.; methyl parahydroxybenzoate, CAS No.: 99-76-3, was purchased from Sigma-Aldrich Trading Co., Ltd.
[0035] Example 1
[0036] A lightweight multifunctional stone-like paint comprises the following raw materials in parts by weight:
[0037] 60 parts of modified latex, 40 parts of red rubber latex, 50 parts of active filler, 1 part of hydroxyethyl cellulose, 8 parts of antifreeze agent, 4 parts of film-forming aid, 1 part of preservative, 1 part of pH regulator, 450 parts of natural colored sand, 1 part of thickener, and 100 parts of deionized water.
[0038] The modified latex is prepared by compounding modified acrylic latex and styrene in a mass ratio of 1:2; the modified acrylic latex is prepared by the following method:
[0039] A1. Weigh the following raw materials in parts by weight: 30 parts of methyl methacrylate, 15 parts of 2-ethylhexyl acrylate, 8 parts of hexafluorobutyl methacrylate, 5 parts of 4-allyloxy-2-hydroxybenzophenone, 1 part of sodium dodecylbenzenesulfonate, 6 parts of functional monomers, 0.2 parts of ammonium persulfate, 0.5 parts of saturated sodium dihydrogen phosphate solution and 80 parts of deionized water;
[0040] A2. Sodium dodecylbenzene sulfonate, deionized water, methyl methacrylate, 2-ethylhexyl acrylate, 4-allyloxy-2-hydroxybenzophenone, hexafluorobutyl methacrylate and functional monomer were mixed by weight, and stirred at a rate of 100 rpm for 15 min to obtain a mixed solution a.
[0041] A3. Heat the mixed solution a to 80° C. under a nitrogen atmosphere, add ammonium persulfate and saturated sodium dihydrogen phosphate solution to the mixed solution a, and stir the mixture for 60 min at a stirring rate of 100 rpm to obtain a modified acrylic emulsion.
[0042] Wherein, the functional monomer is prepared by the following method:
[0043] Step 1, 3,4-dimethoxycinnamic acid, 5-chloro-2-mercaptobenzothiazole and dimethylformamide are mixed in a mass ratio of 3:4:40, stirred at 60°C for 6 hours, and the stirring rate is controlled to be 100 rpm. After the reaction is completed, the mixture is cooled to room temperature, the solvent is removed, and anhydrous ethanol is added for recrystallization to obtain an intermediate product;
[0044] Step 2, mixing the intermediate product with anhydrous ethanol in a mass ratio of 10:60, stirring at a rate of 100 rpm for 8 minutes to obtain a mixed solution 1; mixing dimethylformamide, hydroxyl-terminated methyl vinyl silicone oil and sodium hydroxide, stirring at a rate of 100 rpm for 8 minutes to obtain a mixed solution 2; wherein the mass ratio of dimethylformamide, hydroxyl-terminated methyl vinyl silicone oil and sodium hydroxide is 60:0.5:0.1;
[0045] Step 3, weighing mixed solution 1 and mixed solution 2 in a mass ratio of 10:8, adding mixed solution 2 to mixed solution 1 while stirring, controlling the stirring rate to 100 rpm, the temperature to 30°C, stirring and reacting for 6 hours, then adding maleic anhydride, reacting for 25 minutes, cooling to room temperature to obtain a mixed solution, extracting with dichloromethane, then washing with saturated brine for 3 times, and drying at 60°C for 5 hours to obtain a functional monomer; wherein the mass of maleic anhydride is 2% of the mass of mixed solution 1.
[0046] The active filler is prepared by surface treating the filler, specifically, adding the filler to a chitosan acetic acid solution, stirring at 50°C for 6 hours, with a stirring rate of 100 rpm, filtering, and drying at 70°C for 5 hours to obtain the active filler; the mass ratio of the filler to the chitosan acetic acid solution is 1:40, and the chitosan acetic acid solution is compounded by chitosan, acetic acid and deionized water in a mass ratio of 5:10:80.
[0047] The filler is prepared by compounding white bleached beads and hollow microbeads in a mass ratio of 4:1.
[0048] The natural colored sand is compounded by coarse colored sand, medium colored sand and fine colored sand in a mass ratio of 1:10:2, the coarse colored sand is 40 meshes, the medium colored sand is 80 meshes, and the fine colored sand is 120 meshes.
[0049] The present application also provides a production process of a lightweight multifunctional stone-like paint, comprising the following steps:
[0050] S1. Mix hydroxyethyl cellulose, active filler and deionized water, stir evenly, add pH regulator, and stir at a rate of 800 rpm for 15 min to obtain a mixed system;
[0051] S2. Add preservative, antifreeze agent, film-forming aid, modified emulsion and red rubber emulsion to the mixed system in sequence while stirring, and stir at a rate of 500 r / min for 35 min to obtain a base paint;
[0052] S3. Under stirring, add natural colored sand to the base paint, stir evenly, then add thickener, stir at a rate of 500r / min for 20min to obtain a lightweight multifunctional imitation stone paint.
[0053] Among them, the antifreeze agent is ethylene glycol; the film-forming aid is dodecyl alcohol ester; the preservative is methyl paraben; the pH regulator is organic alcohol amine; and the thickener is an associative thickener.
[0054] Example 2
[0055] A lightweight multifunctional stone-like paint comprises the following raw materials in parts by weight:
[0056] 100 parts of modified latex, 60 parts of red rubber latex, 80 parts of active filler, 3 parts of hydroxyethyl cellulose, 15 parts of antifreeze agent, 8 parts of film-forming aid, 3 parts of preservative, 2 parts of organic alcohol amine, 650 parts of natural colored sand, 2 parts of thickener, and 200 parts of deionized water.
[0057] The modified latex is prepared by compounding modified acrylic latex and styrene in a mass ratio of 3:2; the modified acrylic latex is prepared by the following method:
[0058] A1. Weigh the following raw materials in parts by weight: 40 parts of methyl methacrylate, 35 parts of 2-ethylhexyl acrylate, 12 parts of hexafluorobutyl methacrylate, 10 parts of 4-allyloxy-2-hydroxybenzophenone, 3 parts of sodium dodecylbenzenesulfonate, 8 parts of functional monomers, 0.6 parts of ammonium persulfate, 1 part of saturated sodium dihydrogen phosphate solution and 100 parts of deionized water;
[0059] A2. Sodium dodecylbenzene sulfonate, deionized water, methyl methacrylate, 2-ethylhexyl acrylate, 4-allyloxy-2-hydroxybenzophenone, hexafluorobutyl methacrylate and functional monomer were mixed by weight, and stirred at a rate of 200 rpm for 10 min to obtain a mixed solution a.
[0060] A3. Heat the mixed solution a to 100° C. under a nitrogen atmosphere, add ammonium persulfate and saturated sodium dihydrogen phosphate solution to the mixed solution a, and stir the mixture for 90 minutes at a stirring rate of 200 rpm to obtain a modified acrylic emulsion.
[0061] Wherein, the functional monomer is prepared by the following method:
[0062] Step 1, 3,4-dimethoxycinnamic acid, 5-chloro-2-mercaptobenzothiazole and dimethylformamide are mixed in a mass ratio of 5:7:60, stirred at 80°C for 4 hours, and the stirring rate is controlled to be 300 rpm. After the reaction is completed, the mixture is cooled to room temperature, the solvent is removed, and anhydrous ethanol is added for recrystallization to obtain an intermediate product;
[0063] Step 2, mixing the intermediate product with anhydrous ethanol in a mass ratio of 15:70, stirring at a rate of 200 rpm for 5 minutes to obtain a mixed solution 1; mixing dimethylformamide, hydroxyl-terminated methyl vinyl silicone oil and sodium hydroxide, stirring at a rate of 200 rpm for 5 minutes to obtain a mixed solution 2; wherein the mass ratio of dimethylformamide, hydroxyl-terminated methyl vinyl silicone oil and sodium hydroxide is 70:1:0.2;
[0064] Step 3, weighing mixed solution 1 and mixed solution 2 in a mass ratio of 10:12, adding mixed solution 2 to mixed solution 1 while stirring, controlling the stirring rate to 200 rpm and the temperature to 40°C, stirring and reacting for 4 hours, then adding maleic anhydride, reacting for 35 minutes, cooling to room temperature to obtain a mixed solution, extracting with dichloromethane, washing with saturated brine 5 times, and drying at 80°C for 3 hours to obtain a functional monomer; wherein the mass of maleic anhydride is 2.5% of the mass of mixed solution 1.
[0065] The active filler is prepared by surface treating the filler, specifically, adding the filler to the chitosan acetic acid solution, stirring at 70°C for 4 hours, stirring at a rate of 200 rpm, filtering, and drying at 90°C for 3 hours to obtain the active filler; the mass ratio of the filler to the chitosan acetic acid solution is 4:60, and the chitosan acetic acid solution is compounded by chitosan, acetic acid and deionized water in a mass ratio of 7:15:90.
[0066] The filler is prepared by compounding white bleached beads and hollow microbeads in a mass ratio of 6:2.
[0067] The natural colored sand is compounded by coarse colored sand, medium colored sand and fine colored sand in a mass ratio of 2:12:4, the coarse colored sand is 60 meshes, the medium colored sand is 100 meshes, and the fine colored sand is 140 meshes.
[0068] The present application also provides a production process of a lightweight multifunctional stone-like paint, comprising the following steps:
[0069] S1. Mix hydroxyethyl cellulose, active filler and deionized water, stir evenly, add pH regulator, and stir at a rate of 1000 rpm for 15 min to obtain a mixed system;
[0070] S2. Add preservative, antifreeze agent, film-forming aid, modified emulsion and red rubber emulsion to the mixed system in sequence while stirring, and stir at a rate of 600 r / min for 25 min to obtain a base paint;
[0071] S3. Under stirring, add natural colored sand to the base paint, stir evenly, then add thickener, stir at a rate of 600r / min for 20min to obtain a lightweight multifunctional imitation stone paint.
[0072] Among them, the antifreeze agent is ethylene glycol; the film-forming aid is dodecyl alcohol ester; the preservative is methyl paraben; the pH regulator is organic alcohol amine; and the thickener is an associative thickener.
[0073] Example 3
[0074] A lightweight multifunctional stone-like paint comprises the following raw materials in parts by weight:
[0075] 80 parts of modified latex, 50 parts of red rubber latex, 60 parts of active filler, 2 parts of hydroxyethyl cellulose, 8 parts of antifreeze agent, 6 parts of film-forming aid, 2 parts of preservative, 1 part of pH regulator, 630 parts of natural colored sand, 0.2 parts of thickener, and 160 parts of deionized water.
[0076] The modified latex is prepared by compounding modified acrylic latex and styrene in a mass ratio of 1:1; the modified acrylic latex is prepared by the following method:
[0077] A1. Weigh the following raw materials in parts by weight: 35 parts of methyl methacrylate, 25 parts of 2-ethylhexyl acrylate, 10 parts of hexafluorobutyl methacrylate, 7 parts of 4-allyloxy-2-hydroxybenzophenone, 2 parts of sodium dodecylbenzenesulfonate, 7 parts of functional monomer, 0.4 parts of ammonium persulfate, 0.8 parts of saturated sodium dihydrogen phosphate solution and 90 parts of deionized water;
[0078] A2. Sodium dodecylbenzene sulfonate, deionized water, methyl methacrylate, 2-ethylhexyl acrylate, 4-allyloxy-2-hydroxybenzophenone, hexafluorobutyl methacrylate and functional monomer were mixed by weight, and stirred at a rate of 150 rpm for 13 min to obtain a mixed solution a.
[0079] A3. Heat the mixed solution a to 90° C. under a nitrogen atmosphere, add ammonium persulfate and saturated sodium dihydrogen phosphate solution to the mixed solution a, and stir the mixture for 75 minutes at a stirring rate of 150 rpm to obtain a modified acrylic emulsion.
[0080] Wherein, the functional monomer is prepared by the following method:
[0081] Step 1, 3,4-dimethoxycinnamic acid, 5-chloro-2-mercaptobenzothiazole and dimethylformamide are mixed in a mass ratio of 4:5:50, stirred at 70°C for 5 hours, and the stirring rate is controlled to be 200 rpm. After the reaction is completed, the mixture is cooled to room temperature, the solvent is removed, and anhydrous ethanol is added for recrystallization to obtain an intermediate product;
[0082] Step 2, mixing the intermediate product with anhydrous ethanol in a mass ratio of 12:65, stirring at a stirring rate of 150 rpm for 7 minutes to obtain a mixed solution 1; mixing dimethylformamide, hydroxyl-terminated methyl vinyl silicone oil and sodium hydroxide, stirring at a stirring rate of 150 rpm for 6 minutes to obtain a mixed solution 2; wherein the mass ratio of dimethylformamide, hydroxyl-terminated methyl vinyl silicone oil and sodium hydroxide is 65:0.8:0.1;
[0083] Step 3, weighing mixed solution 1 and mixed solution 2 in a mass ratio of 10:11, adding mixed solution 2 to mixed solution 1 while stirring, controlling the stirring rate to 150 rpm, the temperature to 35°C, stirring and reacting for 5 hours, then adding maleic anhydride, reacting for 30 minutes, cooling to room temperature to obtain a mixed solution, extracting with dichloromethane, then washing with saturated brine 4 times, and drying at 70°C for 4 hours to obtain a functional monomer; wherein the mass of maleic anhydride is 2.3% of the mass of mixed solution 1.
[0084] The active filler is prepared by surface treating the filler, specifically, adding the filler into a chitosan acetic acid solution, heating and stirring for 5 hours, filtering and drying to obtain the active filler; the mass ratio of the filler to the chitosan acetic acid solution is 3:50, and the chitosan acetic acid solution is compounded by chitosan, acetic acid and deionized water in a mass ratio of 6:13:85.
[0085] The filler is prepared by compounding white bleached beads and hollow microbeads in a mass ratio of 4:2.
[0086] The natural colored sand is a compound of coarse colored sand, medium colored sand and fine colored sand in a mass ratio of 1.5:11:3, the coarse colored sand is 50 mesh, the medium colored sand is 90 mesh, and the fine colored sand is 130 mesh.
[0087] The present application also provides a production process of a lightweight multifunctional stone-like paint, comprising the following steps:
[0088] S1. Mix hydroxyethyl cellulose, active filler and deionized water, stir evenly, add pH regulator, and stir at a rate of 900 rpm for 20 min to obtain a mixed system;
[0089] S2. Add preservative, antifreeze agent, film-forming aid, modified emulsion and red rubber emulsion to the mixed system in sequence while stirring, and stir at a rate of 550 r / min for 30 min to obtain a base paint;
[0090] S3. Under stirring, add natural colored sand to the base paint, stir evenly, then add thickener, stir at a rate of 550r / min for 23min, and obtain a lightweight multifunctional imitation stone paint.
[0091] Among them, the antifreeze agent is ethylene glycol; the film-forming aid is dodecyl alcohol ester; the preservative is methyl paraben; the pH regulator is organic alcohol amine; and the thickener is an associative thickener.
[0092] Comparative Example 1
[0093] Comparative Example 1 is the same as Example 1, except that the filler is white bleached beads.
[0094] Comparative Example 2
[0095] Comparative Example 2 is the same as Example 1, except that the filler is hollow microspheres.
[0096] Comparative Example 3
[0097] Comparative Example 3 is the same as Example 1, except that the modified latex is replaced by a modified acrylic latex.
[0098] Comparative Example 4
[0099] Comparative Example 4 is the same as Example 1, except that the modified acrylic emulsion is replaced with a commercially available acrylic emulsion.
[0100] Comparative Example 5
[0101] Comparative Example 5 is the same as Example 1, except that the preparation method of the functional monomer is different, as follows:
[0102] Functional monomers are prepared by the following method:
[0103] Step 1, 3,4-dimethoxycinnamic acid, 5-chloro-2-mercaptobenzothiazole and dimethylformamide are mixed in a mass ratio of 3:4:40, stirred at 60°C for 6 hours, and the stirring rate is controlled to be 100 rpm. After the reaction is completed, the mixture is cooled to room temperature, the solvent is removed, and anhydrous ethanol is added for recrystallization to obtain an intermediate product;
[0104] Step 2, the intermediate product is mixed with dimethylformamide, stirred at 100 rpm and 30°C for 15 min, maleic anhydride is added, reacted for 25 min, cooled to room temperature to obtain a mixed solution, extracted with dichloromethane, washed with saturated brine for 3 times, and dried at 60°C for 5 h to obtain a functional monomer; wherein the mass ratio of the intermediate product, dimethylformamide and maleic anhydride is 10:60:1.4.
[0105] Comparative Example 6
[0106] Comparative Example 6 is the same as Example 1, except that the preparation method of the functional monomer is different, as follows:
[0107] Functional monomers are prepared by the following method:
[0108] Step 1, 3,4-dimethoxycinnamic acid, 5-chloro-2-mercaptobenzothiazole and dimethylformamide are mixed in a mass ratio of 3:4:40, stirred at 60°C for 6 hours, and the stirring rate is controlled to be 100 rpm. After the reaction is completed, the mixture is cooled to room temperature, the solvent is removed, and anhydrous ethanol is added for recrystallization to obtain an intermediate product;
[0109] Step 2, mixing the intermediate product with anhydrous ethanol in a mass ratio of 10:60, stirring at a rate of 100 rpm for 8 minutes to obtain a mixed solution 1; mixing dimethylformamide, hydroxyl-terminated methyl vinyl silicone oil and sodium hydroxide, stirring at a rate of 100 rpm for 8 minutes to obtain a mixed solution 2; wherein the mass ratio of dimethylformamide, hydroxyl-terminated methyl vinyl silicone oil and sodium hydroxide is 60:0.5:0.1;
[0110] Step 3, weigh mixed solution 1 and mixed solution 2 with a mass ratio of 10:8, add mixed solution 2 to mixed solution 1 while stirring, control the stirring rate to 100 rpm, the temperature to 30°C, stir the reaction for 6 hours and then cool to room temperature to obtain a mixed solution, extract with dichloromethane, wash with saturated brine 3 times, and dry at 60°C for 5 hours to obtain a functional monomer.
[0111] Comparative Example 7
[0112] Comparative Example 7 is the same as Example 1, except that the preparation method of the modified acrylic emulsion is different, as follows:
[0113] The modified acrylic emulsion is prepared by the following method:
[0114] A1. Weigh the following raw materials in parts by weight: 30 parts of methyl methacrylate, 15 parts of 2-ethylhexyl acrylate, 8 parts of hexafluorobutyl methacrylate, 5 parts of 4-allyloxy-2-hydroxybenzophenone, 1 part of sodium dodecylbenzenesulfonate, 0.2 parts of ammonium persulfate, 0.5 parts of saturated sodium dihydrogen phosphate solution and 80 parts of deionized water;
[0115] A2. Sodium dodecylbenzene sulfonate, deionized water, methyl methacrylate, 2-ethylhexyl acrylate, 4-allyloxy-2-hydroxybenzophenone and hexafluorobutyl methacrylate were mixed by weight, and stirred at a rate of 100 rpm for 15 min to obtain a mixed solution a.
[0116] A3. Heat the mixed solution a to 80° C. under a nitrogen atmosphere, add ammonium persulfate and saturated sodium dihydrogen phosphate solution to the mixed solution a, and stir the mixture for 60 min at a stirring rate of 100 rpm to obtain a modified acrylic emulsion.
[0117] Performance Testing
[0118] The performance tests were conducted on the lightweight multifunctional stone-like paints prepared in Examples 1-3 and Comparative Examples 1-7:
[0119] Thermal insulation performance: Refer to GB / T25261-2018 "Reflective thermal insulation coatings for buildings" to test the thermal insulation temperature difference with the reference blackboard;
[0120] Waterproof performance: Use A4 printing paper as the bearing base, use 1mm thick sponge tape to stick out an area of 20cm long and 10cm wide, use a trowel to fill the test sample into the area and level it, weigh it after curing at room temperature for one week, then hang the sample at an angle of 75°, use a drip device to continuously wet the middle of the paint surface, and observe whether the A4 paper is soaked after 4 hours;
[0121] Hiding power test: simulate outdoor wall construction on the construction site with the same putty and primer (black base), and calculate the consumption per square meter after covering the base layer;
[0122] Aging resistance test: refer to GB / T1865-2009 for aging resistance test.
[0123] The test results are shown in Table 1 and Table 2:
[0124] Table 1 Performance tests of Examples 1-3 and Comparative Examples 1-7
[0125]
[0126] It can be seen from the test results in Table 1 that the imitation stone paints prepared in Examples 1-3 have excellent waterproof performance and aging resistance. After the functional monomers are introduced, the aging resistance and waterproof performance of the imitation stone paints are significantly improved.
[0127] Table 2 Performance tests of Examples 1-3 and Comparative Examples 1-7
[0128]
[0129] It can be seen from the test results in Table 2 that the imitation stone paints prepared in Examples 1-3 have strong construction properties, can be sprayed in one go, have high spraying efficiency, and have good covering effects; after the introduction of white bleached beads, hollow microbeads, and functional monomers, the thermal insulation properties of the imitation stone paints are significantly improved, and the quality is significantly reduced.
[0130] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A lightweight multifunctional stone-like paint, characterized in that: The invention comprises the following raw materials in parts by weight: 60-100 parts of modified latex, 40-60 parts of red rubber latex, 50-80 parts of active filler, 1-3 parts of hydroxyethyl cellulose, 8-15 parts of antifreeze agent, 4-8 parts of film-forming aid, 1-3 parts of preservative, 1-2 parts of pH regulator, 450-650 parts of natural colored sand, 1-2 parts of thickener and 100-200 parts of deionized water.
2. A lightweight multifunctional stone-like paint according to claim 1, characterized in that: The modified latex is prepared by compounding a modified acrylic latex and styrene in a mass ratio of 1-3:
2.
3. A lightweight multifunctional stone-like paint according to claim 2, characterized in that: The modified acrylic emulsion is prepared by the following method: A1. Weigh the following raw materials in parts by weight: 30-40 parts of methyl methacrylate, 15-35 parts of 2-ethylhexyl acrylate, 8-12 parts of hexafluorobutyl methacrylate, 5-10 parts of 4-allyloxy-2-hydroxybenzophenone, 1-3 parts of sodium dodecylbenzenesulfonate, 6-8 parts of functional monomers, 0.2-0.6 parts of ammonium persulfate, 0.5-1 parts of saturated sodium dihydrogen phosphate solution and 80-100 parts of deionized water; A2. Mix sodium dodecylbenzene sulfonate, deionized water, methyl methacrylate, 2-ethylhexyl acrylate, 4-allyloxy-2-hydroxybenzophenone, hexafluorobutyl methacrylate and functional monomer in parts by weight, and stir for 10-15 minutes to obtain a mixed solution a. A3. Heat the mixed solution a to 80-100° C. under protective gas, add ammonium persulfate and saturated sodium dihydrogen phosphate solution to the mixed solution a, stir and react for 60-90 minutes to obtain a modified acrylic emulsion.
4. A lightweight multifunctional stone-like paint according to claim 3, characterized in that: The functional monomer is prepared by the following method: Step 1, 3,4-dimethoxycinnamic acid, 5-chloro-2-mercaptobenzothiazole and dimethylformamide are mixed, heated and stirred for 4-6 hours, cooled to room temperature, the solvent is removed, and anhydrous ethanol is added for recrystallization to obtain an intermediate product, wherein the mass ratio of 3,4-dimethoxycinnamic acid, 5-chloro-2-mercaptobenzothiazole and dimethylformamide is 3-5:4-7:40-60; Step 2, mixing the intermediate product with anhydrous ethanol, stirring evenly to obtain a mixed solution 1; mixing dimethylformamide, hydroxyl-terminated methyl vinyl silicone oil and sodium hydroxide, stirring for 5-8 minutes, to obtain a mixed solution 2; Step 3, weighing mixed solution 1 and mixed solution 2 in a mass ratio of 10:8-12, adding mixed solution 2 to mixed solution 1, stirring and reacting for 4-6 hours, then adding maleic anhydride, reacting for 25-35 minutes, cooling to obtain a mixed solution, extracting, washing, and drying to obtain a functional monomer.
5. A lightweight multifunctional stone-like paint according to claim 4, characterized in that: The mass ratio of the intermediate product to anhydrous ethanol in step 2 is 10-15:60-70; the mass ratio of dimethylformamide, hydroxyl-terminated methyl vinyl silicone oil and sodium hydroxide in step 2 is 60-70: 0.5-1:0.1-0.2; the mass of maleic anhydride in step 3 is 2-2.5% of the mass of the mixed solution 1.
6. The lightweight multifunctional stone-like paint according to claim 1, characterized in that: The active filler is prepared by surface treating the filler, specifically, adding the filler into chitosan acetic acid solution, heating and stirring for 4-6 hours, filtering and drying to obtain the active filler; the mass ratio of the filler to the chitosan acetic acid solution is 1-4:40-60.
7. A lightweight multifunctional stone-like paint according to claim 6, characterized in that: The filler is prepared by compounding white bleached beads and hollow microbeads in a mass ratio of 4-6:1-2.
8. The lightweight multifunctional stone-like paint according to claim 1, characterized in that: The natural colored sand is compounded by coarse colored sand, medium colored sand and fine colored sand in a mass ratio of 1-2:10-12:2-4, the coarse colored sand is 40-60 meshes, the medium colored sand is 80-100 meshes, and the fine colored sand is 120-140 meshes.
9. A production process of a lightweight multifunctional stone-like paint as claimed in any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Mix hydroxyethyl cellulose, active filler and deionized water, stir evenly, add pH regulator, and continue stirring for 15-25 minutes to obtain a mixed system; S2. Add preservative, antifreeze agent, film-forming aid, modified emulsion and red rubber emulsion to the mixed system in sequence while stirring, and stir for 20-30 minutes to obtain a base paint; S3. Add natural colored sand to the base paint while stirring, stir evenly, then add thickener and stir for 20-25 minutes to obtain lightweight and multifunctional imitation stone paint.